SANIRI RESILIENCE IN THE DYNAMICS OF MONOCULTURAL POLICY - Suharno, Suharno; Milwan, Milwan (International Journal of Psychosocial Rehabilitation, 2020)
The condition of people in Maluku with multicultural dimensions has the potential to cause conflict and is actually proven by the Ambon Conflicts 1999-2000 and 2011. These conflicts, both potential and actual, must be managed to minimize the chance of escalation into destructive conflict. In that context, the Saniri indigenous institution is local wisdom that can be instrumented to maintain harmony and social cohesion in Maluku society. This institution has a crucial position because Saniri is used as a means of multicultural conflict resolution. Saniri's local wisdom is proven to have the ability to survive, especially in monocultural policies during the New Order. Saniri resilience is influenced by several factors: namely, socio-cultural, legal, political, and environmental.